Various Tribes of Indonesian Students Have a Spirit of High Solidarity for Tolerance in RAS, Religion and Culture in Indonesia - Anif Luthfia Valentina (International Journal of Business and Applied Economics, 2023)
Praise be expressed to the presence of Allah SWT. We can analyze the many tribes of Indonesian students who have a high spirit of solidarity, not a minority, to tolerate race, religion, and culture in Indonesia, which is a difference that exists in Indonesia without being divided.  Therefore, we thank God for all His grace so that this paper can be compiled. until finish. We do not forget to express our gratitude for the assistance of those who   have   contributed   by   contributing   both thoughts and materials. The author really hopes that this article can add knowledge and experience to readers. In fact, we hope even further that this article can be practiced by readers in everyday life. For us as the authors feel that there are still many shortcomings in the preparation of this paper due to limited knowledge and experience.  For this reason, we really hope for constructive criticism and suggestions from readers for the perfection of this article.